2-Acetoxybriaranes from Briareum violaceum. Issue 27 (5th July 2019) - Yao, Jia-Wen; Chi, Wei-Chiung; Lee, Gene-Hsiang; Su, Jui-Hsin; Hwang, Tsong-Long; Wu, Yu-Jen; Su, Tzu-Rong; Sheu, Jyh-Horng; Sung, Ping-Jyun
Abstract: Five 2-acetoxybriaranes, including two known analogues, excavatolides B (1 ), E (2 ), along with three new metabolites, briaviolides V–X (3 –5 ), have been obtained from the octocoral Briareum violaceum . The absolute configurations of1 and2 were determined by X-ray analysis for the first time and the structures of3 –5 were established by spectroscopic methods. Bioactivity study showed that briarane3 decreased the release of elastase from human neutrophils. Graphical abstract: Image 1